PRODUKTIVITAS DAN EFISIENSI PRODUKSI GONDORUKEM DI BEBERAPA PABRIK DI JAWA TENGAH Productivity and Efficiency of Several Collophonium Factories in Central Java - Sylviani Sylviani (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Collcfohonium industries in Cen'tralJava are potential enough to be developed • a• source of income for people liuirw near the forest a well a for Perum Perhutani.Bated on the study at several collophonium factories, the averagelabourproductivity for administl'ativelab(!urandtechnician were 742 ton/man and 121,8 tori/man rapeetively. Jlaclainaryeflkiency averageWal 72 %, and that for material Wal, 189 %. The avm11te ef'/fciency for Coat used by private tac,torywaa 1,86 and.for Perum Perhutani 1,83. Actual total ost spent were Rp. 83,886,288 and Rp. 90,27'!,158,ctively, for factories run by private sector and Perum Perhutani.